Light harvesting nanomaterials - Singh, Surya Prakash (Bentham Books, 2015)
Mankind's search for alternative energy sources to oil and gas reserves has been fueled by increasing energy demands and technological developments. Today, the prospect of harvesting energy from new sources is a major issue in scientific and economic discourse and will remain to be so in the future decades to come. Sunlight is known as a reliable and renewable energy source which can be utilized to meet forthcoming energy demand if it is exploited in an efficient manner. Light harvesting nanomaterials represent one way in which this can be achieved through biomimetics or artificially designed.